Determination of cysteinyl leukotrienes in exhaled breath condensate: method combining immunoseparation with LC-ESI-MS/MS - Syslová, Kamila; Kačer, Petr; Vilhanová, Beáta; Kuzma, Marek; Lipovová, Petra; Fenclová, Zdeňka; Lebedová, Jindřiška; Pelclová, Daniela (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2011)
A rapid and precise method for the identification and quantification of cysteinyl leukotrienes (leukotriene C(4), leukotriene D(4) and leukotriene E(4)), essential markers of bronchial asthma, in exhaled breath condensate was developed. The protocol consists of immunoaffinity separation and a detection step, liquid chromatography combined with electrospray ionization tandem mass spectrometry (LC-ESI-MS/MS). In particular, the selected reaction monitoring mode was used for its extremely high degree of selectivity and the stable-isotope-dilution assay for its high precision of quantification. The developed method was characterized with a high precision (≤ 7.7%, determined as RSD), an acceptable accuracy (90.4-93.7%, determined as recovery), a low limit of detection (≤ 2 pg/ml EBC) and a low limit of quantification (≤ 10 pg/ml EBC). It was compared to other simple, clinically appropriate combinations of pre-treatment methods (solid phase extraction and lyophilization) with LC/MS. Finally, the method (a combination of immunoaffinity separation with LC-MS) was successfully tested in a clinical study where a significant difference was found in the concentration levels of cysteinyl leukotrienes between patients with occupational bronchial asthma and healthy subjects.
Keywords: Exhalation; Immunoassay; chromatografie kapalinová; Humans; bronchiální astma; Asthma; hmotnostní spektrometrie s elektrosprejovou ionizací; leukotrieny; mladý dospělý; Chromatography, Liquid; imunoanalýza; mužské pohlaví; Adolescent; vydechnutí; Spectrometry, Mass, Electrospray Ionization; ženské pohlaví; dechové testy; Breath Tests; Cysteine; lidé; mladiství; Leukotrienes; Male; Young Adult; cystein; Female